A contemporary view on obesity treatment in adults - V.I. Velychko; B.M. Mankovskyi; T.F. Tatarchuk; D.O. Lahoda; I.M. Todurov; O.M. Lishchyshyna (Publishing House TRILIST, 2021)
Today, the prevalence of overweight and obesity is pandemic. This disorder is defined as "a complex chronic disease in which abnormal or excess body fat impairs health, increases the risk of long-term medical complications, and decreases life expectancy". This article presents evidence-based clinical guidelines for the management of obese patients, as well as excerpts comments on pharmacological treatment. Treatment approaches for overweight and obese patients include behavioral interventions, lifestyle adjustments, etc. One of the methods is pharmacological therapy, based on the following principles: therapy for weight loss can be used starting already at a body mass index ≥ 27 kg/m2 or ≥ 30 kg/m2 with complications associated with excess body fat. As drugs can be used liraglutide, combination of naltrexone + bupropion, orlistat. Pharmacotherapy must be accompanied by lifestyle modification, including if necessary therapeutic diet, increased physical activity on ongoing basis with its mandatory control, and behavioral or cognitive-behavioral therapy. Pharmacotherapy can be used to support the weight loss achieved through lifestyle modifications and to prevent weight gain. It is forbidden to use over-the-counter drugs unless they are approved for weight control. Patients with metabolic obesity should be consulted by specialists to assess the feasibility of bariatric surgery, followed by treatment with this specialist. Every clinician must have sufficient knowledge to diagnose obesity and offer their patients an individualized, long-term, evidence-based weight loss regimen. The success of obesity treatment depends on the patient's trust the doctor and on the doctor's knowledge in this area.